TEXT OF THE SONG AND ITS POETICS - DAVRONOVA MAKHFUZA ISROILOVNA (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In every era, song has been the spiritual food of peoples. That’s why they paid attention to the song genre even in BC. However, we cannot observe such features or aspects when it comes to its text or poetics. In this article, the poetry of Muhammad Yusuf, who has an important role in the art of Uzbek singing, is studied through on the base of this features. Muhammad Yusuf’s poems became important at the end of the 20th century. The poems he created began to be sung by singers.The poet focuses on the rhythm that creates musicality in his poems. That’s why his poems quickly turn into songs. In addition, the poet pays attention to the linguistic features and content of the poem, and as a result, the songs begin to sound like a work rich in artistic content. In this article, such features are researched and the place of Muhammad Yusuf’s poetry in Uzbek singing is defined.